Pengaruh Perilaku Konsumen Terhadap Keputusan Pembelian Pecel Lele di Sepanjang Jalan Riau Kota Pekanbaru - Trisna Wijayanti; Lamun Bathara; Eni Yulinda (JURNAL SOSIAL EKONOMI PESISIR, 2022)
This study aims to determine the effect of consumer behavior, namely culture (X1), social (X2), psychological (X3), and personal (X4) on purchasing decisions (Y) and the strategies used by catfish pecel traders.The research method used in this research is a survey method, Meanwhile, the determination of consumer respondents for pecel catfish is done by accidental sampling, namely by taking 5 consumers in one pecel catfish outlet with a total number of consumer respondents of 150 consumers and 30 traders of pecel catfish. Based on the results of research and analysis that has been conducted, it is found that the influence of consumer behavior on purchasing decisions is known from the value of Fcount greater than Ftable, namely 149.261> 1.98, and with an R Square value of 0.805, it means 80.5% Y can be explained X1, X2, X3, X4. While the remaining 19.5% can be explained by other factors not examined in this study.